“RUMAH PANGGUNG” FOR THE SETTLEMENT WITH SEA LEVEL RISE PROBLEM IN THE FISHERMEN SETTLEMENT OF TAMBAK LOROK SEMARANG - Edi Purwanto (JOURNAL OF COASTAL DEVELOPMENT, 2010)
Global warming is the natural phenomenon caused by increased glasshouse gases and thinned ozone layer in the atmosphere. The increasing temperature of the earth causes climate change and sea level rise. Some coastal regions in Indonesia have suffered because of it, and the greater impact is on the people’s life because their activities in the settlement of coastal city are influenced directly or indirectly by this natural phenomenon. With the conditions as mentioned above, Indonesia as the biggest archipelago state in the world with its long coastal region seems to experience significant loss. The loss suffered by coastal houses because of sea level rise can be the loss of the physical functions and the investment of the houses. If the impact of sea level rise can be anticipated, so the loss can be prevented by conducting adaptation on natural changes that last slowly by, for example, making dams and utilizing the rumah panggung model. The use of rumah panggung is chosen as one of the solutions to deal with the impact of sea level rise in the troubled settlement of fishermen, Tambak Lorok Semarang, because the area experiences the tide for around 80 days in a year. The other benefit of rumah panggung is to minimize the negative impact, such as the physical damage of houses, humid house environment, and the material of the house cannot last longer. Besides, rumah panggung can use bamboo as local material, which is available with reasonable price.